Effectiveness of Early Exercise Against Uterine Involution in Spontaneous Postpartum Patients - Eny Pemilu Kusparlina; Sundari Sundari (Alliance oh Health Activists (AloHA), 2019)
Background: It is estimated that 50% of puerperal mortality occur within the first 24 hours. At this time the involution process occured. Involutionary disorders cause complications which is the leading cause of maternal mortality. Most of postpartum women do not obtain exercise guidance after giving birth. They are only advised to do simple mobilization without planned guidance. The purpose of this study was to determine the effectiveness of early exercise against uterine involution (fundus and lochea). Methods: The research used quasi experimental (pre-post test non equivalent control group design). It was conducted from January to June 2019. The samples were 40 respondents spontaneous primiparous postpartum mother. The study was started by 1) divided the samples into control group and treatment group, 2) measured the fundus and lochea, 3) provided early exercise on treatment group, 4) re-measured fundus and lochea in both groups, 5) analyzed the effectiveness of early exercise to fundus and lochea expenditure decrease. The data analysis used Mann Whitney with α = 0.05. Results: The results showed p-value of 0.000 (fundus) and 0.001 (lochea). Conclusion: Early exercise is effective in accelerating decrease in fundus and lochea expenditure as it helps blood circulation to the uterine, which causes the uterus to contract well. Good contractions help narrowing of open blood vessels so that bleeding does not occur, decreases in uterine fundus and lochea expendment take place more rapidly. Keywords: early exercise; uterine involution; spontaneous postpartum